2001
DOI: 10.1783/147118901101195281
|View full text |Cite
|
Sign up to set email alerts
|

Termination of pregnancy: Patients' perceptions of care

Abstract: Summary Background. Little is known about women's perceptions of care in termination of pregnancy (TOP).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 4 publications
0
21
0
Order By: Relevance
“…1,3,4 The National Health Service (NHS) Plan requires each NHS Trust in England to obtain feedback from patients about their experiences of care 5 but there has been little work to date on women's experience of abortion services. Questionnaire surveys provide some information [6][7][8][9] but cannot provide a detailed account of women's experience of this procedure, and in-depth qualitative data are scarce. [10][11][12] Data on the experience of women using the NHS abortion service in three inner London boroughs are presented, from the time the women suspected that they were pregnant until their first visit for assessment prior to the abortion procedure.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4 The National Health Service (NHS) Plan requires each NHS Trust in England to obtain feedback from patients about their experiences of care 5 but there has been little work to date on women's experience of abortion services. Questionnaire surveys provide some information [6][7][8][9] but cannot provide a detailed account of women's experience of this procedure, and in-depth qualitative data are scarce. [10][11][12] Data on the experience of women using the NHS abortion service in three inner London boroughs are presented, from the time the women suspected that they were pregnant until their first visit for assessment prior to the abortion procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Younger women 1,2,6 , women with higher levels of education 2 and women without children 1,6 were more likely to report negative experiences of abortion care. Experiences of long waiting time 2,5,7 , inadequacies in treatment by clinicians and health care staff 2,3,5,7 and medical complications in relation to the abortion 1 are examples of health care-related factors. One researcher suggested that to increase satisfaction with abortion services for women undergoing surgical abortion the waiting time at the clinic should be shortened 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Experiences of long waiting time 2,5,7 , inadequacies in treatment by clinicians and health care staff 2,3,5,7 and medical complications in relation to the abortion 1 are examples of health care-related factors. One researcher suggested that to increase satisfaction with abortion services for women undergoing surgical abortion the waiting time at the clinic should be shortened 7 . For women having medical abortion, the provision of adequate and realistic information about bleeding, pain, expulsions and related factors is important and has been stressed in several studies [3][4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] However, very few large-scale studies examine the patients' psychological experience of abortion. 7 Gathering evidence of women's experiences of abortion is a difficult terrain to negotiate partly because the stigma associated with abortion militates against women's disclosure. 8 Accordingly, women who have elected to undergo abortion may not welcome contact about their experience and they may be reluctant to participate in research studies about abortion.…”
Section: Introductionmentioning
confidence: 99%